Reassessing the Cost-Effectiveness of High-Provitamin A Bananas to Reduce Vitamin A Deficiency in Uganda - Kozicka, Marta; Elsey, Julia; Ekesa, Beatrice; Ajambo, Susan; Kikulwe, Enoch; Gotor, Elisabetta (Frontiers in Sustainable Food Systems, 2021)
There are two high-provitamin A (pVA) banana-based interventions potentially available in Uganda—biofortified genetically modified (GM) banana and fast-tracked banana landraces from outside Uganda that are naturally high in provitamin A (nHpVA). Based on the newest country statistics and using adoption scenarios obtained through focus group discussions and expert interviews, we assess obstacles and opportunities for adoption as well as cost-effectiveness of these interventions. In two alternative scenarios for the GM banana (M9 matooke), we assume 40% and 64% adoption rates, which would result in US29,374,151 and US63,259,415 in income saved, respectively. As an alternative, for the symmetrical scenarios, we calculate that if the nHpVA banana (Apantu plantain, native of Ghana) were to be adopted, US46,100,148 and US76,364,988 in income would be saved. Taking into account the full cost of R&D, we estimate that the M9 matooke could save one disability-adjusted life year (DALY) at a cost of US67.37 at best and US145.09 at worst. We estimate that the Apantu plantain could save one DALY at a cost of US50.54 at best and US83.72 at worst. Our DALY analysis estimates that all assessed HpVA banana interventions are extremely cost-effective in all scenarios, following both the World Bank's and the WHO criteria. Nevertheless, successful interventions would require extensive promotion campaigns and shifts in agricultural value chains.